Virtual Bodies and Sport Activities: The case of the Avatars in Second Life Fitness Club - Patsantaras, Nikolaos; Irene Kamberidou (13th Conference of the European Sociological Association “Un)Making Europe: Capitalism, Solidarities, Subjectivities”, 2017)
Virtual environments (VE) are virtual social spaces that provide powerful means for creating, activating and modifying virtual bodies—Avatars—without dependencies on biological factors,formal rules and explicit conventions. VE offer unlimited possibilities to create the desired body and express personal bodily preference in virtual sport spaces without restrictions regarding established roles and behavioural expectations. Such a VE is Second Life (SL) in which the user is represented by an Avatar. This study focuses on a virtual sport space: the Fitness Club of Second Life. It examines the rules and regulations of this virtual space along with the role of 26 Avatars as bodily representations, including their bodily behaviours-exercises-practices in the SL Fitness Club. The data for this study was selected through systematic observation of 26 Avatars (apx. 180 hours) during March, April and May 2015, followed by detailed descriptions of single phenomena. Regarding the structure of space and bodily behavior, the results indicate less differences between sport virtual spaces and sport physical spaces, the opposite of what we had originally assumed. According to the results, the Avatar Fitness Club appears to be a highly individualistic and narcissistic environment. Moreover, every user can perform his/her bodily activities in a rather liberating way, occasionally surpassing biological limitations. When the Avatars exercise they imitate the movements of the physical sport world, namely they mimic the physical body. Further studies are needed to show the influence of an Avatar’s performance-bodily exercises on the real user, the individual behind the computer screen.